Parental awareness in early education fostering child development - Joy, Kanak Shrma; Ferdous, Tamanna; Popy, Fatema Begum; Shafiq, Md. Shahriar (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study analyzes early childhood education (ECE) parental knowledge and active participation across Bangladesh particularly looking at their effects on child intellectual and social and emotional progress. It conducted detailed interviews using a qualitative methodology to understand the opinions of 30 parents who had children between 4 and 6 years old within various socio-economic environments and geographic locations. The analysis showed that higher ECE awareness among parents led to better childhood development support but parent choices were mainly determined by their social background and educational level as well as their evaluation of institutional quality. Education awareness levels among urban families surpass rural families and most disadvantaged parents show little knowledge about pre-primary education. Parents chose ECE institutions based on child-focused settings and qualified educators as well as play-based learning methods. Research evidence shows the critical role which parents play in children’s early education success which requires specific interventions for broadening knowledge and accessibility. The recommendations endorse community-based pre-primary programs while improving educational training for teachers and expanding quality pre-primary education services for families without sufficient resources. The findings serve as a basis to create inclusive policies that will strengthen parental involvement in ECE so Bangladesh can achieve development equality for children.